Snow Avalanches in Forested Terrain: Influence of Forest Parameters, Topography, and Avalanche Characteristics on Runout Distance - Teich, Michaela; Bartelt, Perry; Grêt-Regamey, Adrienne; id_orcid:0 000-0001-8156-9503; Bebi, Peter (Arctic, Antarctic, and Alpine Research, 2012)
ISSN:1523-0430 ISSN:1938-4246